Modellierung von Zweifel – Vorbild TEI im Graphen - Andreas Kuczera; Dominik Kasper (Zeitschrift für digitale Geisteswissenschaften)
The focus of the imports of TEI documents from the German Text Archive (DTA) into a graph database (Neo4j) evaluated here is the marking of uncertain readings and editorial additions in manuscripts. In this context, we also briefly present the TEI guidelines for dealing with doubts and uncertainties. Since several people usually work in editing or transcription projects, we regard responsibility information at dubious points as central to the interoperability of data and the intersubjective traceability of individual decisions. This applies in particular if additional information on the degree of security of a resolution is possible. Graph technologies offer possibilities for modeling, visualization and analysis of uncertainty and responsibility. With a sufficiently large amount of data, personal labeling profiles of the respective editors can be created, for example.